Tax Morale and Compliance Behavior: First Evidence on a Causal Link - Martin Halla (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2010)
Recent literature on tax evasion emphasizes the importance of moral considerations to explain compliance behavior. As a consequence scholars aim to identify factors that shape this so-called tax morale. However, the causal link between tax morale and actual compliance behavior is not established yet. Exploiting exogenous variation in tax morale - given by the inherited part of tax morale of American-born from their ancestors country of origin - our instrumental variable analysis provides first evidence on a causal effect of tax morale on the size of the underground production.
Keywords: A13; O17; H26; Z13; C81; 330; Tax morale; tax evasion; tax compliance; underground production